Associated Complications and survival rate after thyroid cancer operation - Hamad Mustafa , Dilshad; Saeed Ahmed , Baderkhan (Diyala Journal of Medicine, 2023)
Background: Thyroid cancer is a common endocrine neoplasm in all parts of the world and the commonest histologic type is PTC. The Treatment of choice for this pathology is surgery and it has associated complications commonly hypocalcaemia and RLNP with specific survival rates. Objective: To find out the incidence of associated complications of thyroid surgery with their survival rates. Patients and Methods: We analysed data from 574 patients diagnosed with TC from 2018 to 2021, using the Kaplan-Meier method and log-rank test to determine complications of thyroid surgery and overall survival. Results: The mean age of the patients was 41.3 (±14.1) years, there were 92(16%) patients aged >55 years and 482(84%) patients ≤ 55 years old at the time of diagnosis. Females were more affected by the female: male ratio (3.9: 1); 456 cases occurred in females (79.4%) and 118 in males (20.6%). The most common modes of presentation were neck lump in 492 (85.7%) patients and tumor size ≤4 cm in 495(86.3) patients. The commonest stage at diagnosis is stage I 494(86.1%), of the cases confined to the thyroid gland. The main surgical procedure was total thyroidectomy for 470(81.9%) patients. The common complications are hypocalcemia 70(12.6%) and 46(8.3%) developed RLN damage. The mean survival time was (55.87) months (CI = 54.86-56.88 months), but varies according to age < 55 years (58.02 months) and ≥ 55 years (44.426 months). Sex female has a better prognosis (56.540 months) while males (52.40 months). stage I mean survival was (58.79months) while a decrease in stage IV mean survival was (23.36 months). Conclusion: The incidence of complications associated with TC surgery in our study is close to what was published elsewhere in the world with slight differences in percentages of each complication. The survival rate drops within the available ranges.